Design-a-trial: a rule-based decision support system for clinical trial design - Nammuni, K; Pickering, C; Modgil, S; Montgomery, A; Hammond, P; Wyatt, J; Altman, D; Dunlop, R; Potts, H (2004)
The complexity of clinical research has meant that clinical trial protocols are often scientifically and ethically unsound. Trial designers often have limited statistical skills and experience in clinical research. This problem is exacerbated in the academic arena, in which access to statistical expertise is limited. Design-a-Trial (DaT) is an expert system that assists trial designers in designing and planning clinical trials. The system is developed in Visual Basic.NET and Prolog, and is due for commercial release in September 2003. The main aim of DaT is to help trial designers with limited statistical and research experience to design scientifically and ethically sound trials. It also serves as a checklist for the more experienced designers and can potentially be used to assist in the training of new clinical researchers. © 2004 Elsevier B.V. All rights reserved.